KETERAMPILAN GURU DALAM KONSEP PENDEKATAN DALAM PENGELOLAAN KELAS MENURUT AHLI - Siagian, Inneke Putri; Nisa, Khairun; Ayuni, Sity Qurrota; Novita Sari, Widya (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2022)
In short, in a class there are various different characters from each student, so that it has the opportunity to trigger various kinds of problems that can interfere with learning activities. Because these problems occur in the classroom, the relationship is with classroom management carried out by the teacher. In managing the class, teachers are required to have skills in the concept approach. The purpose of this research is to describe the skills of teachers in the conceptual approach to classroom management. The research method used is a literature study with a qualitative approach, which is sourced from reference books, journals, and others. Classroom management is an effort directed at creating an effective and fun learning atmosphere so that students can be well motivated. The results of the study show that the teacher's skills in the concept of an appropriate classroom management approach will create a quality learning process. So it can be concluded that teacher skills play an important role in the learning process, especially in creating a conducive climate class, so as to create meaningful and enjoyable learning, and achieve learning goals effectively and efficiently.